Synthesis of new condensed naphthoquinone, pyran and pyrimidine furancarboxylates - Gomonov, Kirill A.; Pelipko, Vasilii V.; Litvinov, Igor A.; Pilipenko, Ilya A.; Stepanova, Anna M.; Lapatin, Nikolai A.; Baichurin, Ruslan I.; Makarenko, Sergei V. (Beilstein Journal of Organic Chemistry, 2025)
New representatives of dioxodihydronaphtho[2,3-b]furan-, furo[3,2-c][1]benzopyran-, furo[2,3-d]pyrano[4,3-b]pyran-, furo[2',3':4,5]pyrano[3,2-c]chromene-, and furo[2,3-d]pyrimidine carboxylates were obtained from the reactions of alkyl 3-bromo-3-nitroacrylates with representatives of carbo- and heterocyclic CH-acids under simple conditions, without the use of organocatalysts. The structures of the synthesized compounds were proven by a set of physicochemical methods, including X-ray diffraction analysis.
Keywords: CH-acids; 1-halo-1-nitroethenes; heterocyclization; nitroacrylates; X-ray diffraction analysis